2015
DOI: 10.1016/j.gdata.2015.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Transcription profiling of the Neurospora crassa response to a group of synthetic (thio)xanthones and a natural acetophenone

Abstract: Xanthones are a class of heterocyclic compounds characterized by a dibenzo-γ-pyrone nucleus. Analysis of their mode of action in cells, namely uncovering alterations in gene expression, is important because these compounds have potential therapeutic applications. Thus, we studied the transcriptional response of the filamentous fungus Neurospora crassa to a group of synthetic (thio)xanthone derivatives with antitumor activity using high throughput RNA sequencing. The induction of ABC transporters in N. crassa, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 26 publications
(51 reference statements)
0
10
0
Order By: Relevance
“…In Kluyveromyces lactis , a fungus more closely related to S. cerevisiae than to N. crassa , deletion of ERG6 (encoding C-24 sterol methyl transferase) can also activate the expression of the CDR4 homolog ( Konecna et al, 2016 ), providing another supporting evidence to the transcriptional activation induced by defects in ergosterol biosynthesis. Thus, the transcriptional induction of cdr4 in N. crassa by compounds, such as xanthone derivatives, might be caused by their inhibition on ergosterol biosynthesis ( Pinto et al, 2011 ; Pedro Gonçalves et al, 2015 ). Interestingly, DTT and avicel, which can induce ER stress, also activate the expression of cdr4 in N. crassa ( Coradetti et al, 2013 ; Fan et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In Kluyveromyces lactis , a fungus more closely related to S. cerevisiae than to N. crassa , deletion of ERG6 (encoding C-24 sterol methyl transferase) can also activate the expression of the CDR4 homolog ( Konecna et al, 2016 ), providing another supporting evidence to the transcriptional activation induced by defects in ergosterol biosynthesis. Thus, the transcriptional induction of cdr4 in N. crassa by compounds, such as xanthone derivatives, might be caused by their inhibition on ergosterol biosynthesis ( Pinto et al, 2011 ; Pedro Gonçalves et al, 2015 ). Interestingly, DTT and avicel, which can induce ER stress, also activate the expression of cdr4 in N. crassa ( Coradetti et al, 2013 ; Fan et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In 2020, to further explore the mode of action of 22 in cells, as well as other structure related(thio)xanthones with antitumor activity, the transcriptional response of the filamentous fungus Neurospora crassa to these compounds using high throughput RNA sequencing was evaluated. These compounds showed to induce genes which express ABC transporters in N. crassa , particularly atrb and cdr4, and to repress genes that are evocative of genes downregulated during oxidative stress [ 94 ].…”
Section: A Library Of Natural Mimetic Xanthones Looking For Biologmentioning
confidence: 99%
“…Furthermore, no significant differences were detected in the activity of the enantiomeric pairs towards P-gp [ 181 ]. Still concerning P-gp induction in other organisms, using high throughput RNA sequencing, the transcriptional response of the filamentous fungus Neurospora crassa to thioxanthone derivatives with antitumor activity ( 75 , 81 , and 86 ) revealed that there is an induction of ABC transporters in that fungus, particularly atrb and cdr4, which is a common consequence of the treatment with (thio)xanthones [ 94 ]. Moreover, a group of genes were downregulated by the tested thioxanthones during oxidative stress [ 94 ].…”
Section: A Library Of Natural Mimetic Xanthones Looking For Biologmentioning
confidence: 99%
See 1 more Smart Citation
“…6 ). Gene expression data for putative Pth11-related GPCRs was mined from publically available datasets, including experiments of GSE65311 [ 30 ] and GSE49597 [ 31 ] for biotic stress, GSE37886 [ 32 ], GSE21908 [ 33 ], and GSE33683 [ 34 ] for invasive plant infection, and GSE43006 [ 35 ], GSE53040 [ 36 ], GSE42692 [ 37 ], and GSE46155 [ 38 ] for nutritional stress. RNA-seq data for H. oryzae were also used to study the invasive infection of plants by H. oryzae [ 27 ].…”
Section: Resultsmentioning
confidence: 99%